A Study to Compare the Diagnostic Accuracy of CT and USG in the Diagnosis of Acute Appendicitis - Veeresh Hanchinal; S Rutuparna; Priyanka Patil (Asian Journal of Medical Radiological Research, 2021)
Background: Vague abdomen pain is the most commonly encountered symptom in the emergency department at any hospital. The various cause of the abdomen pain may vary from benign to life threatening disease. Appendicitis is the most common cause of abdomen pain in patients admitted at the emergency department. The Aim of the study was to evaluate the accuracy of CT and USG in the diagnosis of acute appendicitis in patients who are taken for appendectomy on clinical basis. Subjects and Methods: A Prospective Observational study was conducted at Department of Radiology at Gadag Institute of medical Sciences from June 2019 to December 2019. A total of 200 study subjects during the study period who presented with symptoms of acute abdomen pain and clinical findings highly suspicious of appendicitis were enrolled for the purpose of the study. Result : From the study it is concluded that CT is more sensitive, specificity, PPV, NPV. Hence the CT investigation is more accuracy than USG in diagnosing cases of appendicitis. Conclusion: Evaluating a case of appendicitis is mainly clinical, depending on the clinical scores and signs. But there is increase in the negative appendectomy rate on depending only on clinical findings. Usually USG is the first primary techniques, considering its easy availability, low cost and reproducible with no radiation but it has its own pitfalls, being operator dependent. CT on the other hand is more specific than USG and hence could rule out appendicitis. Most of the studies including our study has shown that CT has more sensitivity, specificity, Negative predictive value and Positive predictive value in diagnosing appendicitis.